Immune checkpoint inhibitors plus capecitabine and oxaliplatin in unresectable or advanced biliary tract cancer patients: A retrospective study - Zhao, Jie; Guo, Yongzhong; Ding, Wenzhou; Han, Guoyong; Jiang, Chuanwei; Yang, Chao; Hu, Yuanchang; Zhang, Long; Wu, Chen; Ni, Ming; Kong, Xiangyi; Huang, Tian; et al. (Frontiers in Oncology, 2022)
Objective: Immune checkpoint inhibitors (ICIs) have recently been increasingly used in cancer treatment, whereas their clinical application in biliary tract cancer (BTC) patients is uncommon. This study aimed to evaluate the efficacy and safety of ICIs plus capecitabine and oxaliplatin (CAPOX) in the treatment of BTC patients. Methods: This retrospective study reviewed 26 unresectable or advanced BTC patients who received ICIs plus CAPOX. The treatment continued until disease progression, uncontrollable adverse events (AEs) occurrence, intolerable toxicity occurrence, or voluntary withdrawal. Results: The median treatment cycles were 5.5 (interquartile range (IQR): 3.8-8.0). Complete response, partial response, stable disease, and progressive disease rates were 0.0%, 46.2%, 23.1%, and 30.8%, respectively. Objective response rate (ORR) and disease control rate (DCR) were 46.2% and 69.2%, correspondingly. Regarding survival, the median progression-free survival (PFS) and overall survival (OS) were 6.1 (95%CI: 4.4-7.7) months and 16.5 (95%CI: 5.0-28.0) months; moreover, the 1-year PFS and OS rates were 21.5% and 54.3%, respectively. Eastern Cooperative Oncology Group (ECOG) score of 1-3 (vs. 0) was associated with declined DCR, PFS, and OS (all P<0.050). The most common AEs of ICIs plus CAPOX were thrombocytopenia (61.5%), neutropenia (26.9%), and reactive cutaneous capillary endothelial proliferation (RCCEP) (23.1%). Besides, 13 (50.0%) patients suffered from grade 3-4 AEs, including thrombocytopenia (50.0%), neutropenia (7.7%), liver dysfunction (7.7%) and RCCEP (3.8%). Notably, the majority of adverse events were controllable. Conclusion: ICIs plus CAPOX chemotherapy exhibit a good efficacy and a manageable safety profile in the treatment of patients with unresectable or advanced BTC.